Universidade na comunidade - Lima, Maria José de Oliveira [UNESP]; Piana, Maria Cristina [UNESP]; Guimarães, Orlinéya Maciel [UNESP]; Sousa, Júlia Fonseca de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Extension Project " University in the Community" aims to ensure conditions for effective citizenship , through social and educational activities directed at students of the third grade of elementary school public school located in Franca / SP, to facilitate the interest and access to public university . The project was created in order to bring the local community information and guidance on the university, higher education, forms of integration and the policies of student remained. It is also proposed to provide opportunities to encourage the choice of high school students for the courses offered by UNESP, which contributes to the expansion of the dissemination of these courses in the local community

O Projeto de Extensão “Universidade na Comunidade” visa garantir condições para a efetivação da cidadania, através de ações socioeducativas direcionadas aos alunos do terceiro ano do ensino médio de escola pública estadual E.E. Prof Ângelo Gosuen, situada em Franca/SP, visando facilitar o interesse e o acesso à Universidade Pública. O projeto foi criado com intuito de levar à comunidade local, informações e orientações sobre a universidade, Ensino Superior, as formas de inserção e as políticas de permanência estudantil. Também se propõe oferecer oportunidades para incentivar a escolha do aluno do ensino médio para os cursos ofertados pela UNESP, o que contribui para a ampliação da divulgação destes cursos na comunidade local.
Keywords: Public university; Higher education; Public permanence student policies; Universidade pública; Educação superior; Políticas públicas de permanência estudantil